LEPTON MASSES IN AN SU(3)L-CIRCLE-TIMES-U(1)N GAUGE-MODEL - Foot, R.; Hernandez, O. F.; Pisano, F.; PLEITEZ, V (American Physical Soc, 1993)
The SU(3)cxSU(3)LxU(1)N model of Pisano and Pleitez extends the standard model in a particularly nice way, so that, for example, the anomalies cancel only when the number of generations is divisible by 3. The original version of the model has some problems accounting for the lepton masses. We resolve this problem by modifying the details of the symmetry-breaking sector in the model.